Advances in the human side of service engineering : proceedings of the AHFE 2017 International Conference on The Human Side of Service Engineering, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on The Human Side of Service Engineering, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available